2012
DOI: 10.1103/physrevb.86.035102
|View full text |Cite
|
Sign up to set email alerts
|

Strong renormalization of the Fermi-surface topology close to the Mott transition

Abstract: The underlying Fermi surface is a key concept for strongly-interacting electron models and has been introduced to generalize the usual notion of the Fermi surface to generic (superconducting or insulating) systems. By using improved correlated wave functions that contain backflow and Jastrow terms, we examine the two-dimensional t−t ′ Hubbard model and find a non-trivial renormalization of the topology of the underlying Fermi surface close to the Mott insulator. Moreover, we observe a sharp crossover region, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
6
25
0
Order By: Relevance
“…By contrast, within the insulating phase, the intra-orbital Jastrow factor is larger than the inter-orbital one, implying that configurations with two electrons on the same orbital are penalized with respect to the ones with two electrons on different orbitals, as expected in the presence of a finite value of J. Only for small values of J/U , a (nearest-neighbor intra-orbital) singlet pairing with d x 2 −y 2 symmetry can be stabilized (see Fig 1), similarly to what occurs in the single-band Hubbard model at half filling [14,48]. Most importantly, a strong (onsite inter-orbital) triplet pairing ∆ ⊥ is stabilized by the presence of a finite Hund coupling, giving a sizable gain in the variational energy with respect to the case with no pairing (see also Sec.…”
Section: Resultsmentioning
confidence: 63%
“…By contrast, within the insulating phase, the intra-orbital Jastrow factor is larger than the inter-orbital one, implying that configurations with two electrons on the same orbital are penalized with respect to the ones with two electrons on different orbitals, as expected in the presence of a finite value of J. Only for small values of J/U , a (nearest-neighbor intra-orbital) singlet pairing with d x 2 −y 2 symmetry can be stabilized (see Fig 1), similarly to what occurs in the single-band Hubbard model at half filling [14,48]. Most importantly, a strong (onsite inter-orbital) triplet pairing ∆ ⊥ is stabilized by the presence of a finite Hund coupling, giving a sizable gain in the variational energy with respect to the case with no pairing (see also Sec.…”
Section: Resultsmentioning
confidence: 63%
“…This is very similar to the case of the two-dimensional single-orbital Hubbard model with including up to the second nearest neighbor hoppings at half filling (n = 1) where the FS of the corresponding |Φ is deformed to the tilted square shape satisfying the perfect nesting condition. 68 When the non-interacting FS of H 0 is far from the square (as in Fig. 1 with additional hole pockets), the metal-insulator transition occurs before the FS deformation is completed with increasing Coulomb interactions.…”
Section: -67mentioning
confidence: 99%
“…For the single plane, different methods predict that the system becomes a Mott insulator at some finite U, as shown for instance in reference [29], where the critical U was calculated using the dynamical cluster approximation with a variety of cluster sizes. Also, Tocchio et al [30] and Capello et al [31] showed with the VMC method (which in the first reference includes Fermi surface renormalization effects) the appearance of a Mott insulator at a finite U. A possible reason for the occurrence of a Mott insulator for any finite U in reference [9] might be the small cluster size of × 2 2 used in cluster DMFT.…”
Section: ∑∑mentioning
confidence: 99%